2013
DOI: 10.1212/wnl.0b013e31829e0fdd
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital stroke care

Abstract: Brain cells die rapidly after stroke and any effective treatment must start as early as possible. In clinical routine, the tight time-outcome relationship continues to be the major limitation of therapeutic approaches: thrombolysis rates remain low across many countries, with most patients being treated at the late end of the therapeutic window. In addition, there is no neuroprotective therapy available, but some maintain that this concept may be valid if administered very early after stroke. Recent innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 58 publications
0
70
0
1
Order By: Relevance
“…31 The new 4G technology with higher bandwidth and optional prioritization in public mobile networks appears to be more appropriate for the use of ambulance-based telestroke applications. 13,32 A streamlined unassisted telestroke scale 33 was evaluated with healthy volunteers mimicking stroke syndromes during ambulance transportation 34 and demonstrated sufficient stability in a moving ambulance using 4G connectivity. Further testing in actual acute stroke transport situations is needed to assess this promising approach.…”
Section: January 2017mentioning
confidence: 99%
“…31 The new 4G technology with higher bandwidth and optional prioritization in public mobile networks appears to be more appropriate for the use of ambulance-based telestroke applications. 13,32 A streamlined unassisted telestroke scale 33 was evaluated with healthy volunteers mimicking stroke syndromes during ambulance transportation 34 and demonstrated sufficient stability in a moving ambulance using 4G connectivity. Further testing in actual acute stroke transport situations is needed to assess this promising approach.…”
Section: January 2017mentioning
confidence: 99%
“…The available evidence has demonstrated that mHealth could optimize the care and recovery of patients with myocardial infarction and stroke, aid in the screening and management of cognitive impairment, and facilitate sleep monitoring and intervention [18][19]. Moreover, mHealth may offer solutions to accessible and good quality individualized health management services to improve the management of chronic diseases through remote monitoring and enhance awareness and diseases-specific education.…”
Section: Clinical Applications Of Mhealth For Aging-related Neurologimentioning
confidence: 99%
“…Hence, patients' stroke type can be quickly and accurately diagnosed, and thrombolytic therapy can be used during the transport process [26]. According to a random survey of the equipment, the implementation of STEMO pre-hospital treatment can shorten median medical decision-making time from 76 minutes to 35 minutes [19]. Obviously, this type of luxury equipment is not suitable for developing countries.…”
Section: Strokementioning
confidence: 99%
“…However, significant limitations exist with regard to prehospital management, timely selection for intravenous tPA or endovascular therapy, and multidisciplinary coordination of posttreatment stroke and ICU care. 4,6 Perhaps most importantly, both intravenous thrombolysis and mechanical revascularization target vessel recanalization rather than tissue reperfusion and are highly dependent on time.…”
Section: Neurosurg Focus 42 (4):e4 2017mentioning
confidence: 99%
“…However, significant limitations exist with regard to prehospital management, timely selection for intravenous tPA or endovascular therapy, and multidisciplinary coordination of posttreatment stroke and ICU care. 4,6 Perhaps most importantly, both intravenous thrombolysis and mechanical revascularization target vessel recanalization rather than tissue reperfusion and are highly dependent on time.Despite recent advances, the rates of functional independence (14%-58%) following mechanical thrombectomy are poor compared with the efficient rates of recanalization (60%-90%). 7,34 The mechanism underlying this paradox remains elusive.…”
mentioning
confidence: 99%